A gust of WNT: analysis of the canonical WNT pathway - Giunta, S. (Acta Biomedica Atenei Parmensis, 2009)
The Wnt pathway is a signal-transduction cascade that mediates communication between cells; the Wnt pathway is involved in key steps during embryological development and in the maintenance of adult tissue homeostasis. Mutational dysregulation of Wnt cascade components has been observed in diverse human pathological conditions and in oncogenic transformations. For these reasons, the Wnt signalling pathway has acquired growing interest in scientific and medical research over recent years. This review outlines the biochemical and functional features of the Wnt cascade with particular emphasis on a detailed functional analysis of all key players. In this instance, the regulations of the pathway have also been covered, emphasizing novelty in this regard. Furthermore, past and present studies on Wnt have been included, as well as a prediction of scientific progress, which may be made in this rapidly evolving field, in the near future; the review also embraces considerations on how further understanding of the Wnt pathway will provide important insight into managing human diseases.